Global, regional, and national burden of Alzheimer's disease and other dementias, 1990–2019 - Li, Xue; Feng, Xiaojin; Sun, Xiaodong; Hou, Ningning; Han, Fang; Liu, Yongping (Frontiers in Aging Neuroscience, 2022)
Background With the increase in the aging population worldwide, Alzheimer's disease has become a rapidly increasing public health concern. Monitoring the dementia disease burden will support health development strategies by providing scientific data. Methods Based on data obtained from the 2019 Global Burden of Disease (GBD) database, the numbers and age-standardized rates (ASRs) of incidence, prevalence, death and disability-adjusted life-years (DALYs) of Alzheimer's disease and other dementias from 1990 to 2019 were analyzed. Calculated estimated annual percentage changes (EAPCs) and Joinpoint regression analyses were performed to evaluate trends during this period. We also evaluated the correlations between the epidemiology with the sociodemographic index (SDI), an indicator to evaluate the level of social development in a country or region that considering the education rate, economic situation and total fertility rate. Results From 1990 to 2019, the incidence and prevalence of Alzheimer's disease and other dementias increased by 147.72% and 160.89%, respectively. The ASR of incidence, prevalence, death, and DALYs in both men and female consistently increased over the study period. All the ASRs in female were consistently higher than those in men, but the increases were more pronounced in men. In addition, the ASRs of incidence, prevalence, and DALYs were positively correlated with the SDI. Moreover, the proportion of patients over 70 years old with dementia was also positively correlated with SDI level. Smoking is a major risk factor for the disease burden of dementia in males, while obesity is a major risk factor for females. Conclusions From 1990 to 2019, the Alzheimer’s disease burden increased worldwide. This trend was more serious in high-SDI areas, especially among elderly populations in high-SDI areas, who should receive additional attention. Policy-makers should take steps to reverse this situation. Notably, female were at higher risk for the disease, but the risk in men showed a faster increase. We should give attention to the aging population, attach importance to interventions targeting dementia risk factors, and formulate action plans to address the increasing incidence of dementia.